bookmark_borderIntroduction to Theta Functions II

Infinite product representations of theta functions

Let f(z) = \prod_{n=1}^{\infty} (1-q^{2n-1}e^{2iz})(1-q^{2n-1}e^{-2iz}). Each of these two products converge absolutely and uniformly in any bounded domain of values of z. Hence f(z) is analytic throughout the finite part of the z plane. The zeros of f(z) are simple zeros at the points z=\frac{2n+1}{2}\pi \tau i + m\pi i where m,n\in \mathbb{Z}. So, the zeros of f(z) coincide with the zeros of \vartheta_4(z). Therefore, the function \frac{\vartheta_4(z)}{f(z)} has no poles or zeros in the finite part of the plane. Also, it is easy to see that f(z+\pi) = f(z) and \begin{aligned} f(z+\pi \tau) &= \prod_{n=1}^\infty (1-q^{2n+1}e^{2iz})(1-q^{2n-3}e^{-2iz}) \\ &= f(z) \frac{1-q^{-1}e^{-2iz}}{1-qe^{2iz}} \\ &= -q^{-1}e^{-2iz} f(z) \end{aligned} This is, \frac{\vartheta_4(z)}{f(z)} is a doubly periodic function with periods \pi,\pi\tau and has no poles and zeros. By section 20.12 of [2], it is simply a constant, say G. We have \vartheta_4(z) = G \prod_{n=1}^{\infty} (1-q^{2n-1}e^{2iz})(1-q^{2n-1}e^{-2iz})\quad (1) Incrementing z by the half periods \frac{\pi}{2}, \frac{\pi \tau}{2} and \frac{\pi +\pi\tau}{2}, we get the product representations for the other theta functions: \begin{aligned} \vartheta_3(z) &= G \prod_{n=1}^{\infty} (1+q^{2n-1}e^{2iz})(1+q^{2n-1}e^{-2iz})\quad (2) \\ \vartheta_1(z) &= 2G q^{\frac{1}{4}}\sin(z) \prod_{n=1}^{\infty} (1-q^{2n}e^{2iz})(1-q^{2n}e^{-2iz}) \quad (3) \\ \vartheta_2(z) &= 2G q^{\frac{1}{4}}\cos(z) \prod_{n=1}^{\infty} (1+q^{2n}e^{2iz})(1+q^{2n}e^{-2iz}) \quad (4) \end{aligned} Now, all that left is to find the constant G. From identity (3), it easy to see that \vartheta_1'(0) = 2G q^{\frac{1}{4}}\prod_{n=1}^{\infty} (1-q^{2n})^2 Now, using the identity \vartheta_1'(0)=\vartheta_2(0)\vartheta_3(0)\vartheta_4(0), we get: \begin{aligned} 2G q^{\frac{1}{4}}\prod_{n=1}^{\infty} (1-q^{2n})^2 &= \left\{2G q^{\frac{1}{4}}\prod_{n=1}^{\infty}(1+q^{2n})^2 \right\} \times \left\{G\prod_{n=1}^{\infty}(1+q^{2n-1})^2 \right\} \\ &\quad \times \left\{G \prod_{n=1}^{\infty}(1-q^{2n-1})^2 \right\} \\ \implies G &= \prod_{n=1}^\infty (1-q^{2n}) \end{aligned} Note that the rearrangements are justified since all products converge absolutely. Finally, we have \begin{aligned} \vartheta_1(z) &= 2 q^{\frac{1}{4}}\sin(z) \prod_{n=1}^{\infty} (1-q^{2n})(1-2q^{2n} \cos(2z)+ q^{4n}) \quad (5) \\ \vartheta_2(z) &= 2 q^{\frac{1}{4}}\cos(z) \prod_{n=1}^{\infty} (1-q^{2n})(1+2q^{2n} \cos(2z) + q^{4n}) \quad (6) \\ \vartheta_3(z) &= \prod_{n=1}^{\infty} (1-q^{2n})(1+2q^{2n-1} \cos(2z) + q^{4n-2}) \quad (7) \\ \vartheta_4(z) &= \prod_{n=1}^{\infty} (1-q^{2n})(1-2q^{2n-1} \cos(2z) + q^{4n-2}) \quad (8) \end{aligned}

Derivatives of Ratios of Theta Functions

Consider the function \phi(z) = \frac{\vartheta_1'(z)\vartheta_4(z) - \vartheta_1(z)\vartheta_4'(z)}{\vartheta_2(z)\vartheta_3(z)}. Now, \phi(z) is doubly periodic with periods \pi and \frac{\pi\tau}{2}. Relative to these periods, the only poles of \phi(z) are at points congruent to \pi\over 2. It follows that \phi(z) is a constant. Letting z\to 0, we see that \phi(z)=\vartheta_4^2(0). It is therefore established that \frac{d}{dz}\left(\frac{\vartheta_1(z)}{\vartheta_4(z)} \right)=\vartheta_4^2(0) \frac{\vartheta_2(z)\vartheta_3(z)}{\vartheta_4^2(z)} \quad (9) Two other identities if this kind can be derived using the same technique: \begin{aligned} \frac{d}{dz}\left(\frac{\vartheta_2(z)}{\vartheta_4(z)} \right) &=-\vartheta_3^2(0) \frac{\vartheta_1(z)\vartheta_3(z)}{\vartheta_4^2(z)} \quad (10) \\ \frac{d}{dz}\left(\frac{\vartheta_3(z)}{\vartheta_4(z)} \right) &=-\vartheta_2^2(0) \frac{\vartheta_1(z)\vartheta_2(z)}{\vartheta_4^2(z)} \quad (11) \end{aligned} By writing \xi = \frac{\vartheta_1(z)}{\vartheta_4(z)} and making use of identities (13) and (14) from part 1, we obtain: \left(\frac{d\xi}{dz}\right)^2 = (\vartheta_2^2(0) - \xi^2 \vartheta_3^2(0))(\vartheta_3^2(0)-\xi^2 \vartheta_2^2(0)) Using the change of variables y = \frac{\vartheta_3(0)}{\vartheta_2(0)}\xi and u = \vartheta_3^2(0) z, the above differential equation can be written as: \left(\frac{dy}{du}\right)^2 = (1-y^2)(1-k^2 y^2) where k = \frac{\vartheta_2^2(0)}{\vartheta_3^2(0)}. This differential equation has the particular solution: y = \frac{\vartheta_3(0)}{\vartheta_2(0)} \frac{\vartheta_1(u \vartheta_3^{-2}(0))}{\vartheta_4(u \vartheta_3^{-2}(0))} We can write y as a function of u and k as y = \text{sn}(u,k) or simply \text{sn}(u). Clearly, \text{sn}(u,k) has periods 2\pi \vartheta^2_3(0) and \pi \tau \vartheta_3^2(0). It has two simple poles congruent to \frac{1}{2}\pi\tau \vartheta_3^2(0) and \pi \vartheta_3^2(0) + \frac{1}{2}\pi\tau \vartheta_3^2(0). Also, it is easy to see that \int_0^1 \frac{dy}{\sqrt{(1-y^2)(1-k^2 y^2)}} = \text{sn}^{-1}(1) = \frac{\pi}{2}\vartheta_3^2(0) The integral on the left is denoted by complete elliptic integral of the first kind and is denoted by K(k).


  1. Derek F. Lawden (1989). Elliptic Functions and Applications. Springer-Verlag New York
  2. E. T. Whittaker, G. N. Watson (1927). A Course of Modern Analysis. Cambridge University Press

bookmark_borderIntroduction to Theta Functions I

The Jacobi theta functions are defined for all complex variables of z and q such that |q| < 1, as follows: \begin{aligned} \vartheta_1 (z,q) &= -i \sum_{n=-\infty}^{\infty} (-1)^n q^{(n+1/2)^2} e^{i(2n+1)z} \\ \vartheta_2 (z,q) &= \sum_{n=-\infty}^{\infty} q^{(n+1/2)^2} e^{i(2n+1)z} \\ \vartheta_3 (z,q) &= \sum_{n=-\infty}^{\infty} q^{n^2} e^{2inz} \\ \vartheta_4 (z,q) &= \sum_{n=-\infty}^{\infty} (-1)^n q^{n^2} e^{2inz} \\ \end{aligned} The parameter q is called the nome. Let \tau be a complex number whose imaginary part is positive and write q=e^{i\pi \tau} so that |q| < 1. Sometimes, q will not be specified, so that \vartheta_r (z) is written for \vartheta_r(z,q) where r=1,2,3,4. It is easy to see that \begin{aligned} \vartheta_1(z+\pi) &= -i e^{i \pi}\sum_{n=-\infty}^{\infty}(-1)^n q^{\left(n+\frac{1}{2}\right)^2}e^{i(2n+1)z} = -\vartheta_1(z) \\ \vartheta_1(z+\pi \tau) &= i e^{-i\pi \tau -2iz} \sum_{n=-\infty}^{\infty} (-1)^{n+1} e^{i\pi \tau \left( n+\frac{3}{2}\right)^2 + (2n+3) iz} = - (q e^{2iz})^{-1} \vartheta_1(z) \end{aligned} Similarly, the periodicity laws for the other theta functions can be derived as well. The multipliers of the theta functions associated with the periods \pi and \pi \tau are summarized in the following table: \begin{array}{|c|c|c|c|c|} \hline \; & \vartheta_1(z) & \vartheta_2(z) & \vartheta_3(z) & \vartheta_4(z) \\ \hline \hline \pi & -1 & -1 & 1 & 1 \\ \hline \pi \tau & -\lambda & \lambda & \lambda & -\lambda \\ \hline \end{array} where \lambda = (q e^{2iz})^{-1}. Furthermore, incrementation of z by the half periods \frac{\pi}{2}, \frac{\pi \tau}{2}, \frac{\pi +\pi \tau}{2} yields the following identities: \begin{array}{|c|c|c|c|c|} \hline \omega & \vartheta_1(z+\omega) & \vartheta_2(z+\omega) & \vartheta_3(z+\omega) & \vartheta_4(z+\omega) \\ \hline \hline \frac{\pi}{2} & \vartheta_2(z) & -\vartheta_1(z) & \vartheta_4(z) & \vartheta_3(z) \\ \hline \frac{\pi \tau}{2} & i \mu \vartheta_4(z) & \mu \vartheta_3(z) & \mu \vartheta_2(z) & i\mu \vartheta_1(z) \\ \hline \frac{\pi + \pi \tau}{2} & \mu \vartheta_3(z) & -i\mu \vartheta_4(z) & i\mu \vartheta_1(z) & \mu \vartheta_2(z) \\ \hline \end{array} where \mu = (q^{\frac{1}{4}}e^{iz})^{-1}.

Identities involving products of theta functions

Many theta function identities can be derived by the multiplication of two of their series and rearrangement of the terms in the product series. This is justified since the series are absolutely convergent. We have \begin{aligned} \vartheta_3(x,q)\vartheta_3(y,q) &= \left(\sum_{n=-\infty}^{\infty} q^{n^2} e^{2inx} \right)\left(\sum_{m=-\infty}^{\infty} q^{m^2} e^{2imy} \right) \\ &= \sum_{n=-\infty}^\infty \sum_{m=-\infty}^\infty q^{n^2+m^2}e^{2i(nx+my)} \end{aligned} Now, we change the summation indices from (m,n) to (r,s) by the following equations: \begin{aligned} r &= m+n \\ s &= m-n \end{aligned} If (m,n) are both even then (r,s) will both be even and if (m,n) have opposite parity then (r,s) will both be odd. Therefore, we can rearrange the series as follows: \begin{aligned} \vartheta_3(x,q)\vartheta_3(y,q) &= \sum_{r=-\infty}^{\infty} \sum_{s=-\infty}^{\infty} q^{2(r^2 +s^2)}e^{2i(r(x+y)+s(x-y))} \\ &\quad + \sum_{r=-\infty}^{\infty} \sum_{s=-\infty}^{\infty}q^{2\left[\left(r+\frac{1}{2} \right)^2 + \left(s+\frac{1}{2} \right)^2\right]} e^{i(2r+1)(x+y) + i(2s+1)(x-y)} \\ &= \vartheta_3(x+y,q^2)\vartheta_3(x-y,q^2) + \vartheta_2(x+y,q^2)\vartheta_2(x-y,q^2) \quad (1) \end{aligned} Some similar identities that can be derived using this method are: \begin{aligned} \vartheta_1(x,q) \vartheta_1(y,q) &= \vartheta_3(x+y,q^2)\vartheta_2(x-y,q^2) - \vartheta_2(x+y,q^2)\vartheta_3(x-y,q^2) \quad (2) \\ \vartheta_2(x,q) \vartheta_2(y,q) &= \vartheta_2(x+y,q^2)\vartheta_3(x-y,q^2) + \vartheta_3(x+y,q^2)\vartheta_2(x-y,q^2) \quad (3) \\ \vartheta_4(x,q) \vartheta_4(y,q) &= \vartheta_3(x+y,q^2)\vartheta_3(x-y,q^2) - \vartheta_2(x+y,q^2)\vartheta_2(x-y,q^2) \quad (4) \\ \vartheta_1(x,q) \vartheta_2(y,q) &= \vartheta_1(x+y,q^2)\vartheta_4(x-y,q^2) + \vartheta_4(x+y,q^2)\vartheta_1(x-y,q^2) \quad (5) \\ \vartheta_3(x,q) \vartheta_4(y,q) &= \vartheta_4(x+y,q^2)\vartheta_4(x-y,q^2) - \vartheta_1(x+y,q^2)\vartheta_1(x-y,q^2) \quad (6) \end{aligned} Squaring and subtracting identities (4) and (2) gives us: \begin{aligned} &\; \vartheta_4^2(x,q) \vartheta_4^2(y,q) - \vartheta_1^2(x,q) \vartheta_1^2(y,q)\\ &= \left[\vartheta_3^2(x+y,q^2)-\vartheta_2^2(x+y,q^2) \right]\times \left[\vartheta_3^2(x-y,q^2)-\vartheta_2^2(x-y,q^2) \right] \quad (7) \end{aligned} Putting y=0 in the above equation gives the result: \vartheta_3^2(x,q^2)-\vartheta_2^2(x,q^2) = \vartheta_4(x,q)\vartheta_4(0,q) Now, using the above result in equation (7) gives us: \vartheta_4(x+y,q)\vartheta_4(x-y,q)\vartheta_4^2(0,q) = \vartheta_4^2(x,q) \vartheta_4^2(y,q) - \vartheta_1^2(x,q) \vartheta_1^2(y,q) \quad (8) Note that all theta functions in this equation have the same nome q. More identities of this type can be derived by incrementing x and/or y by the half periods \frac{\pi}{2},\frac{\pi \tau}{2},\frac{\pi+\pi\tau}{2}: \begin{aligned} \vartheta_1(x+y)\vartheta_1(x-y)\vartheta_4^2(0) &= \vartheta_3^2(x) \vartheta_2^2(y) - \vartheta_2^2(x) \vartheta_3^2(y) \\ &= \vartheta_1^2(x) \vartheta_4^2(y) - \vartheta_4^2(x) \vartheta_1^2(y)\quad (9) \\ \vartheta_2(x+y)\vartheta_2(x-y)\vartheta_4^2(0) &= \vartheta_4^2(x) \vartheta_2^2(y) - \vartheta_1^2(x) \vartheta_3^2(y) \\ &= \vartheta_2^2(x) \vartheta_4^2(y) - \vartheta_3^2(x) \vartheta_1^2(y)\quad (10) \\ \vartheta_3(x+y)\vartheta_3(x-y)\vartheta_4^2(0) &= \vartheta_4^2(x) \vartheta_3^2(y) - \vartheta_1^2(x) \vartheta_2^2(y) \\ &= \vartheta_3^2(x) \vartheta_4^2(y) - \vartheta_2^2(x) \vartheta_1^2(y)\quad (11) \\ \vartheta_4(x+y)\vartheta_4(x-y)\vartheta_4^2(0) &= \vartheta_3^2(x) \vartheta_3^2(y) - \vartheta_2^2(x) \vartheta_2^2(y) \\ &= \vartheta_4^2(x) \vartheta_4^2(y) - \vartheta_1^2(x) \vartheta_1^2(y)\quad (12) \\ \end{aligned} One can keep on deriving similar identities by squaring and adding equations (1) and (2) and squaring and subtracting equations (3) and (2). For a complete list of such identities, see section 1.4 of [1]. Another approach to derive theta function identities is to utilize properties of doubly periodic functions. This method is used extensively by [2].

Consider the function: \frac{a \vartheta_1^2(z) + b \vartheta_4^2(z)}{\vartheta_2^2(z)} This is a doubly periodic function with periods \pi and \pi \tau. Furthermore, we can choose the constants a and b such that there is at most one simple pole in every cell. By section 20.13 of [2], such a function is a constant. By appropriately scaling the constants a and b, we can make the function equal to 1. Therefore, there exists a relationship of the form: a \vartheta_1^2(z) + b \vartheta_4^2(z) = \vartheta_2^2(z) To find a and b, we can put z = 0, \frac{\pi\tau}{2}: \begin{aligned} b \vartheta_4^2(0) &= \vartheta_2^2(0) \; \implies b = \frac{\vartheta_2^2(0)}{\vartheta_4^2(0)} \\ a (i \mu\vartheta_4(0))^2 &= (\mu \vartheta_3(0))^2 \; \implies a = -\frac{\vartheta_3^2(0)}{\vartheta_4^2(0)} \end{aligned} Thus, we have obtained the identity: \vartheta_2^2(0) \vartheta_4^2(z) -\vartheta_3^2(0) \vartheta_1^2(z) = \vartheta_4^2(0) \vartheta_2^2(z) \quad (13) A similar technique yields the identity: \vartheta_3^2(0) \vartheta_4^2(z) - \vartheta_2^2(0) \vartheta_1^2(z) = \vartheta_4^2(0) \vartheta_3^2(z) \quad (14) Incrementing z by \frac{\pi}{2} in (11) and (12) gives two additional identities: \begin{aligned} \vartheta_4^2(0) \vartheta_1^2(z) &= \vartheta_2^2(0) \vartheta_3^2(z) - \vartheta_3^2(0) \vartheta_2^2(z) \quad (15) \\ \vartheta_4^2(0) \vartheta_4^2(z) &= \vartheta_3^2(0) \vartheta_3^2(z) - \vartheta_2^2(0) \vartheta_2^2(z) \quad (16) \end{aligned} With these relations one can express any theta function in terms of any other pair of theta functions. Putting z=0 in (16) gives the identity: \vartheta_4^4(0)+\vartheta_2^4(0) = \vartheta_3^4(0)

The identity \vartheta_1'(0)=\vartheta_2(0)\vartheta_3(0)\vartheta_4(0)

This proof is taken from [1]. Differentiating equation (5) with respect to x and substituting x=y=0, we get: \vartheta_1'(0,q) \vartheta_2(0,q) = 2 \vartheta_1'(0,q^2)\vartheta_4(0,q^2) \quad (17) Substituting x=y=0 in equations (3) and (6) gives: \begin{aligned} \vartheta_2^2(0,q) &= 2\vartheta_2(0,q^2) \vartheta_3(0,q^2) \quad (18) \\ \vartheta_3(0,q)\vartheta_4(0,q) &= \vartheta_4^2(0,q^2) \quad (19) \end{aligned} Now, dividing (17) by both (18) and (19) gives \frac{\vartheta_1'(0,q)}{\vartheta_2(0,q)\vartheta_3(0,q)\vartheta_4(0,q)} = \frac{\vartheta_1'(0,q^2)}{\vartheta_2(0,q^2)\vartheta_3(0,q^2)\vartheta_4(0,q^2)} The repeated application of this result gives: \frac{\vartheta_1'(0,q)}{\vartheta_2(0,q)\vartheta_3(0,q)\vartheta_4(0,q)} = \frac{\vartheta_1'(0,q^{2^n})}{\vartheta_2(0,q^{2^n})\vartheta_3(0,q^{2^n})\vartheta_4(0,q^{2^n})} for all positive integers n. Letting n\to\infty in the above equation, we find that: \frac{\vartheta_1'(0,q)}{\vartheta_2(0,q)\vartheta_3(0,q)\vartheta_4(0,q)} = \lim_{q\to 0}\frac{\vartheta_1'(0,q)}{\vartheta_2(0,q)\vartheta_3(0,q)\vartheta_4(0,q)} \quad (19) From the definitions of the theta functions, it is evident that \begin{aligned} \vartheta_1'(0,q) &= 2q^{\frac{1}{4}} + \mathcal{O}(q^{\frac{9}{4}}) \\ \vartheta_2(0,q) &= 2q^{\frac{1}{4}} + \mathcal{O}(q^{\frac{9}{4}}) \\ \vartheta_3(0,q) &= 1 + \mathcal{O}(q) \\ \vartheta_4(0,q) &= 1 + \mathcal{O}(q) \\ \end{aligned} Therefore, the limit in equation (19) equals 1 and \vartheta_1'(0)=\vartheta_2(0)\vartheta_3(0)\vartheta_4(0) is established as desired.


  1. Derek F. Lawden (1989). Elliptic Functions and Applications. Springer-Verlag New York
  2. E. T. Whittaker, G. N. Watson (1927). A Course of Modern Analysis. Cambridge University Press

bookmark_borderWhen is the group of units in the integers modulo n cyclic?

It is easy to see with the help of Bezout’s identity that the integers co-prime to n from the set \{0,1,\cdots, n-1\} form a group under multiplication modulo n. This group is denoted by (\mathbb{Z}/n\mathbb{Z})^* and it’s order is given by the Euler’s Totient function: \varphi(n) = |(\mathbb{Z}/p\mathbb{Z})^*| . Gauss showed that (\mathbb{Z}/n\mathbb{Z})^* is a cyclic group if and only if n=1,2,4,p,p^k or 2p^k, where p is an odd prime and k > 0. It is very easy to verify this for n=1,2 and 4, as one can simply list out all positive integers less than and co-prime to n. So, we will only focus on proving that (\mathbb{Z}/n\mathbb{Z})^* is cyclic for the remaining three cases.

Theorem 1: (\mathbb{Z}/p\mathbb{Z})^* is cyclic if p is a prime.

Proof: Let d_1, d_2, \cdots , d_r be all the possible orders of the elements of (\mathbb{Z}/p\mathbb{Z})^*. Let e=\text{lcm}(d_1, d_2, \cdots, d_r) and factor e=p_1^{a_1} p_2^{a_2}\cdots p_k^{a_k} as a product of distinct prime powers. By the definition of \text{lcm}, for each p_i^{a_i} there is some d_j divisible by it. Since the d_j‘s are orders of elements of (\mathbb{Z}/p\mathbb{Z})^*, there is an element x_i whose order is p_i^{a_i} t. Then, the element y_i = x_i^t has order p_i^{a_i}. Hence, y_1 y_2\cdots y_k has order e. Thus, we have found an element of order e. Therefore, e|p-1. But the polynomial x^e-1 has p-1 roots (\text{mod }p). Since \mathbb{Z}/p\mathbb{Z} is a field, any polynomial of degree e cannot have more than e roots. Therefore, p-1\leq e and we deduce that e=p-1. Thus, we have found an element of order p-1.

Theorem 2: (\mathbb{Z}/p^a \mathbb{Z})^* is cyclic for any a\geq 1 if p is an odd prime.

Proof: For a=1, we are done by Theorem 1. Let g be a primitive root (\text{mod }p). We first find a t such that (g+pt)^{p-1}\not\equiv 1 \; (\text{mod }p^2). If g^{p-1}\not\equiv 1 \; (\text{mod }p^2), then we can take t=0. Otherwise, we can choose t=1. Indeed, we have (g+p)^{p-1}\equiv 1+p(p-1) g^{p-2} \not \equiv 1 \; (\text{mod }p^2). Let g+pt have order d\; (\text{mod }p^a). Then, d|p^a (p-1). Since g is a primitive root modulo p, (p-1) | d. So, d=p^{r-1} (p-1) for some r\leq a. We also know that (g+pt)^{p-1} = 1+p s where s \nmid p. Thus, \begin{aligned} (g+pt)^{p(p-1)} &= (1+ps)^{p} \\ &= \sum_{i=0}^{p} \binom{p}{i} (ps)^i \\ &\equiv 1+p^2 s \; (\text{mod }p^3) \end{aligned} By induction, it follows that (g+pt)^{p^{b-1}(p-1)} \equiv 1+p^b s \; (\text{mod }p^{b+1}) Now, g+pt has order d=p^{r-1}(p-1)\; (\text{mod } p^a) which implies (g+pt)^{p^{r-1}(p-1)} \equiv 1 \; (\text{mod }p^a). But then 1+p^r s \equiv 1 \; (\text{mod } p^{r+1}) if r\leq a-1, which implies p | s, a contradiction. Thus, r=a.

Theorem 3: (\mathbb{Z}/2p^a \mathbb{Z})^* is cyclic for any a\geq 1 if p is an odd prime.

Proof: This follows immediately from Theorem 2 and the Chinese remainder theorem.

The fact that (\mathbb{Z}/n\mathbb{Z})^* can be cyclic only for the cases discussed above can also be verified easily using the Chinese remainder theorem.


  • M. Ram Murty. Problems in analytic number theory. Springer New York, 01-Nov-2008